Cloud Task Scheduling Based on Enhanced Meta Heuristic Optimization Technique - Kaur, N; Kathuria, C; Gupta, D (International Journal of Computer Sciences and Engineering, 2025)
There are number of resources available for the users but user can’t afford these resources as these resources are costly. But users can use these resources on a rental basis. Internet access is readily available everywhere and it can be used by user to access the resources. So the best option available is to use the cloud service. With the growing popularity of cloud services, there come certain challenges. The problem of load balancing is its biggest challenge. Load balancing and task scheduling helps in optimizing various resource related parameters. The idea is to reduce the cost from the customer point of view and then improve the resource utilization from service provider point of view. A number of optimization algorithms have already been proposed for load balancing. This paper proposed an enhanced ACO algorithm for cloud task scheduling that helps to improve the imbalance factor of VM;s and also improve the overall Makespan time.